Prevalence and influencing factors of oral frailty among middle-aged and older patients with chronic kidney disease: a cross-sectional study - Wang, Yuelin; Chen, Zengli; Tang, Qing; Jiang, Yunlan; Cong, Qianqian; Chen, Hong; Wu, Lunhui (Frontiers in Medicine, 2025)
BackgroundOral health has emerged as a subject of significant public concern. Oral frailty represents the clinical presentation of advanced oral health decline and serves as a significant indicator of systemic frailty. However, current research on oral frailty in patients with chronic kidney disease (CKD) is quite limited.ObjectivesThis study aimed to investigate the prevalence and influencing factors of oral frailty among middle-aged and older CKD patients.MethodsThis was a cross-sectional study involving 307 CKD patients from two tertiary general hospitals in Chengdu, Sichuan Province, from November 2024 to March 2025. The Oral Frailty Index-8 (OFI-8), Mini Nutritional Assessment Short-Form (MNA-SF), Revised Piper Fatigue Scale (RPFS) and Hospital Anxiety and Depression Scale (HADS) were used to assess CKD patients. Chi-square tests and logistic regression analyses were used to determine the associated factors of oral frailty among CKD patients.ResultsThe prevalence of oral frailty among CKD patients was 61.9% (190/307). In binary logistic regression analysis, marital status, educational level, self-care ability, dentures, dry mouth, and the RPFS-CV score were identified as factors significantly increasing the risk of oral frailty in middle-aged and older hospitalized patients with CKD.ConclusionCompared with non-CKD patients, CKD patients demonstrate poorer oral health status, and oral frailty is common among CKD patients. This finding suggests the necessity for healthcare professionals to develop individualized and evidence-based strategies for the prevention and management of oral frailty, with particular emphasis on high-risk populations requiring targeted interventions.